Comprehensive kinetic and substrate specificity analysis of an arylsulfatase from Helix pomatia using mass spectrometry. Issue 6 (15th March 2019) - Correia, Mário S.P.; Ballet, Caroline; Meistermann, Hannes; Conway, Louis P.; Globisch, Daniel
Graphical abstract: Abstract: Sulfatases hydrolyze sulfated metabolites to their corresponding alcohols and are present in all domains of life. These enzymes have found major application in metabolic investigation of drugs, doping control analysis and recently in metabolomics. Interest in sulfatases has increased due to a link between metabolic processes involving sulfated metabolites and pathophysiological conditions in humans. Herein, we present the first comprehensive substrate specificity and kinetic analysis of the most commonly used arylsulfatase extracted from the snail Helix pomatia . In the past, this enzyme has been used in the form of a crude mixture of enzymes, however, recently we have purified this sulfatase for a new application in metabolomics-driven discovery of sulfated metabolites. To evaluate the substrate specificity of this promiscuous sulfatase, we have synthesized a series of new sulfated metabolites of diverse structure and employed a mass spectrometric assay for kinetic substrate hydrolysis evaluation. Our analysis of the purified enzyme revealed that the sulfatase has a strong preference for metabolites with a bi- or tricyclic aromatic scaffold and to a lesser extent for monocyclic aromatic phenols. This metabolite library and mass spectrometric method can be applied for the characterization of other sulfatases from humans and gut microbiota to investigate their involvement in disease development.